2015
DOI: 10.4314/mmj.v27i2.2
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Characteristics and the Burden of Altered Nutritional Status among Neuropsychiatric Patients at Zomba Mental Hospital in Zomba, Malawi

Abstract: ObjectiveTo determine the prevalence of overnutrition and undernutrition among neuropsychiatric inpatients and outpatients at Zomba Mental Hospital in Zomba, Malawi. MethodsIn this analytical cross-sectional study (n = 239), data were collected from psychiatric patients who were either inpatients (n = 181) or outpatients (n = 58) at Zomba Mental Hospital, which is the largest mental health facility in Malawi. Information was collected about patient demographics, anthropometric data, dietary information, and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
(12 reference statements)
2
0
0
1
Order By: Relevance
“…From those psychiatric patients having undernutrition, 67 (63.2%) were males. This finding is consistent with a study conducted in Malawi on anthropometric characteristics, and the burden of altered nutritional status among neuropsychiatric patients at Zomba mental hospital had shown that male patients were significantly taller and heavier than females, but had a significantly lower mean BMI than female patients [20,25].…”
Section: Psychiatry Journalsupporting
confidence: 92%
See 1 more Smart Citation
“…From those psychiatric patients having undernutrition, 67 (63.2%) were males. This finding is consistent with a study conducted in Malawi on anthropometric characteristics, and the burden of altered nutritional status among neuropsychiatric patients at Zomba mental hospital had shown that male patients were significantly taller and heavier than females, but had a significantly lower mean BMI than female patients [20,25].…”
Section: Psychiatry Journalsupporting
confidence: 92%
“…Additionally, it can deplete the investments of healthy metabolism and also cause low mood, irritability, and/or aggressive behavior as well as more serious and long-term mental health problems, which further predispose to undernutrition [9]. It is also in line with a study conducted in Malawi on anthropometric characteristics, and the burden of altered nutritional status among neuropsychiatric patients at Zomba mental Hospital had shown that alcohol use are known risk factors for undernutrition [25].…”
Section: Psychiatry Journalsupporting
confidence: 65%
“…A desnutrição está presente em aproximadamente 14% dos pacientes de DEP e DA e em 27,5% dos pacientes de OTP. MHANGO et al, (2015) encontraram prevalência de apenas 8,8% de desnutrição em pacientes adultos jovens de neuropsiquiatria. Pode-se entender com isso, que os idosos nessa condição tenham maior vulnerabilidade para distúrbios do estado nutricional que adultos jovens.…”
Section: Doenças Neuropsiquiátricas E Envelhecimentounclassified